Recovery of zinc and cadmium from spent batteries using Cyphos IL 102 via solvent extraction route and synthesis of Zn and Cd oxide nanoparticles. (September 2017) - Singh, Rashmi; Mahandra, Harshit; Gupta, Bina
Highlights: First time Cyphos IL102 explored for recovery of Zn/Cd from spent batteries. Recovery of metals with high purity was achieved at room temperature. Quantitative extraction was achieved in two stages for Zn and Cd. Loaded organic phases were used to synthesize ZnO and CdO nanoparticles. Simple strippants for stripping isotherm was used. Abstract: The overall aim of this study is to separate and recover zinc and cadmium from spent batteries. For this purpose Cyphos IL 102 diluted in toluene was employed for the extraction and recovery of Zn and Cd from Zn-C and Ni-Cd batteries leach liquor. The influence of extractant concentration for the leach liquors of Zn-C (0.01–0.05 mol/L) and Ni-Cd (0.04–0.20 mol/L) batteries has been investigated. Composition of the leach liquor obtained from Zn-C/Ni-Cd spent batteries is Zn - 2.18 g/L, Mn - 4.59 g/L, Fe - 4.0 × 10 −3  g/L, Ni - 0.2 × 10 −3  g/L/Cd - 4.28 g/L, Ni - 0.896 × 10 −1  g/L, Fe - 0.148 g/L, Co - 3.77 × 10 −3  g/L, respectively. Two stage counter current extraction at A/O 1:1 and 3:2 with 0.04 mol/L and 0.2 mol/L Cyphos IL 102 for Zn and Cd, respectively provide more than 99.0% extraction of both the metal ions with almost negligible extraction of associated metal ions. A stripping efficiency of around 99.0% for Zn and Cd was obtained at O/A 1:1 using 1.0 mol/L HNO3 in two and three counter current stages, respectively. ZnO and CdO were also synthesized using the loaded organic phase and characterized using XRD, FE-SEM and EDX techniques. XRD peaks of ZnO and CdO correspond to zincite and monteponite, respectively. The average particle size was ∼27.0 nm and ∼37.0 nm for ZnO and CdO, respectively. The EDX analysis of ZnO and CdO shows almost 1:1 atomic percentage.